Поселение эпохи бронзы Снежковка-7 на Северском Донце - Берестнев, С. И. (Давнина. Харківський історико-археологічний щорічник, 2016)
Summary Berestnev S. I. Settlement of Bronze Age Snezhkovka-7 on Seversky Donets In the article the materials of bronze age settlements on Seversky Donets of Kharkov region are described. Two chronological horizons. Are defined: late timber-greve dated late XIV-XIII c. B. C. and late catacomb dated to XVII - early XVI c. B. C.